Dari Overthinking Menuju Positive Thinking: Pelatihan Pengelolaan Pikiran Negatif bagi Remaja Masjid "Ijo" Sumbersari - Siti Rochayah; Duwi Sitoresmi; Dewi Masyitoh (Jurnal Mitra Dedikasi Masyarakat, 2026)
Overthinking among adolescents is a psychological issue that may affect mental health and individual adaptive functioning. A needs assessment conducted at Remaja Masjid “Ijo” Sumbersari revealed that 82% of 34 participants exhibited tendencies of overthinking related to academic concerns, social relationships, and future uncertainty. This community service program aimed to enhance adolescents’ understanding of overthinking and develop positive thinking skills as a strategy for managing negative thoughts. The implementation methods included needs assessment, psychoeducation, identification of negative thoughts, positive thinking training, and evaluation and reflection. The results indicated improved participants’ understanding of the relationship between thoughts, emotions, and behaviors, as well as their ability to identify and reconstruct negative thoughts into more rational perspectives. The evaluation showed positive participant responses. The output of the program was a simple guidebook on positive thinking for adolescents. In conclusion, the program is effective as a promotive and preventive intervention to manage overthinking and improve adolescent psychological well-being. Keywords: overthinking, adolescents, positive thinking, psychoeducation, mental healt.